PERAN ADAT LUHAK KEPENUHAN DALAM MENANGANI KENAKALAN REMAJA DI KECAMATAN KEPENUHAN - Utami, Gusmediana; Novarizal , Riky (Gapenas Publisher, 2025)
Juvenile delinquency is a social phenomenon that is often faced by various communities around the world, including Indonesia. Juvenile delinquency can include various forms of negative behavior, such as violations of social norms, minor crimes, drug abuse, and fights between teenagers. Juvenile delinquency in Kepenuhan Sub-district is an issue that needs attention. This condition is not only detrimental to the future of the teenagers involved but also has a negative impact on the social environment and community security. This research aims to find out the stages of solving the problem of juvenile delinquency carried out by the traditional leaders of Luhak Kepenuhan, along with the obstacles. The research method used is qualitative, with data collection techniques through interviews with the Kepenuhan Police, traditional leaders, and the community. The results of this study indicate that the forms of juvenile delinquency in this area include theft, illegal racing, misuse of technology, and other deviant behaviors. The role of adat is preventive through a family approach, such as deliberation and customary advice, but still faces obstacles such as limited funds, low parental participation, and no formal synergy with law enforcement. Based on Travis Hirschi's social control theory, juvenile delinquency is caused by weak social ties, commitment, involvement in positive activities, and belief in social values.